2014
DOI: 10.1007/s10551-014-2401-7
|View full text |Cite
|
Sign up to set email alerts
|

How Green Management Influences Product Innovation in China: The Role of Institutional Benefits

Abstract: Does being green facilitate product innovation? This study examines whether green management in firms operating in China fosters radical product innovation to a greater extent than it does incremental product innovation and investigates the underlying institutional mechanisms involved in the relationship between green management and product innovation. The findings show that green management is more likely to lead to radical product innovation than to incremental product innovation. Moreover, government suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
289
1
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(307 citation statements)
references
References 84 publications
(114 reference statements)
9
289
1
8
Order By: Relevance
“…Third, we focus on the so-called "fateful triangle" of innovation. This approach is gaining importance in the academic sphere (Ballot, Fakhfakh, Galia, & Salter, 2015) because, in addition to the widely analysed product and process innovation (i.e., Kim, Song, Sambamurthy, & Lee, 2012;Martínez-Conesa et al, 2017;Shu et al, 2016), it also considers organizational innovation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we focus on the so-called "fateful triangle" of innovation. This approach is gaining importance in the academic sphere (Ballot, Fakhfakh, Galia, & Salter, 2015) because, in addition to the widely analysed product and process innovation (i.e., Kim, Song, Sambamurthy, & Lee, 2012;Martínez-Conesa et al, 2017;Shu et al, 2016), it also considers organizational innovation.…”
mentioning
confidence: 99%
“…Conceptual model II: CSR dimensions-innovation types link (i.e.,Luo & Du, 2015;Wagner, 2010); the Dow Jones Sustainability Index (i.e.,Gallego-Alvarez et al, 2011); firms' own surveys with choice instruments (i.e.,Curras-Pérez et al, 2018;Martínez-Conesa et al, 2017;Shu et al, 2016); or secondary surveys (i.e.,Bocquet et al, 2013Bocquet et al, , 2017. In this paper, the variables used to measure CSR are organized into three groups, as they are related to the economic, social, or environmental dimensions of CSR.…”
mentioning
confidence: 99%
“…Some authors have suggested that entrepreneurs motivated by ethical concerns may be more successfully in green innovations (York & Venkataraman, 2010). A study by Shu, Zhou, Xiao, and Gao (2016) corroborates the notion that a commitment by firms to transition to green management or natural environment leads to radical innovation rather than incremental innovation. These findings are summarized in our third hypothesis as follows:…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 64%
“…Because a list of firms with the contact information of top managers is not publicly available in China, previous research has often relied on government agencies to obtain such lists (Li, Xie, Teo, & Peng, 2010;Shu, Zhou, Xiao, & Gao, 2016;Walker, Ni, & Huo, 2014). In China, local governments often establish economic development zones that take charge of many firms.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%